SAUDI ARABIA'S DIVERSIFICATION STRATEGY THROUGH THE RED SEA PROJECT IN FACING THE INTERNATIONAL PETROLEUM COMPETITION - Amal, Moh. Talabul; Sahide, Ahmad; Bustami, Mohammad Reevany (Fakultas Syariah, 2024)
This paper examines how legal structures in Saudi Arabia have changed to diversify the economy. In this regard, the focus is on developing the tourism sector through the Red Sea Project. Traditionally, the Saudi economy was largely dependent on oil exports, thus prone to volatile markets and inadequate crude oil reserves. However, the instability in the global oil market has posed a threat to the economy, which led the government to kickstart the Saudi Vision 2030 initiative—a much-sought plan that mainly consists of reforms aimed at revitalizing sectors outside of oil. This research analyses the problem using the Law and Economics theory, and it seeks to investigate how investment laws and environmental laws are used to establish environmentally friendly investment avenues. The findings show that, although Saudi Arabia’s tourism industry has not been able to bring in revenue as oil does, in the long term, the economy's growth under the legal changes brought by Saudi Vision 2030 will bear fruit. Their significance lies in emphasizing the importance of properly developed legal means of firm institutional framework for successfully implementing economic resource diversification in non-renewable resource-rich economies. It also shows how such legal reforms could be applied to pursue economic change in countries with resource economies and could serve as a model for such economies that experience similar problems.Arikel ini mengkaji bagaimana struktur hukum di Arab Saudi telah berubah untuk mendiversifikasi ekonomi dan dalam hal ini, fokusnya adalah pada pengembangan sektor pariwisata melalui Proyek Laut Merah. Secara tradisional, ekonomi Saudi sebagian besar bergantung pada ekspor minyak, sehingga rentan terhadap pasar yang bergejolak dan ketidakcukupan dalam cadangan minyak mentah. Namun, ketidakstabilan di pasar minyak global telah menimbulkan ancaman bagi ekonomi yang menyebabkan pemerintah memulai inisiatif Visi Saudi 2030, sebuah rencana yang banyak dicari yang terutama terdiri dari reformasi yang bertujuan untuk merevitalisasi sektor-sektor di luar minyak seperti pariwisata. Penelitian ini dianalisis menggunakan teori Hukum dan Ekonomi dan mencoba menjawab pertanyaan tentang bagaimana undang-undang investasi dan hukum lingkungan digunakan untuk membangun jalan investasi yang ramah lingkungan. Temuan menunjukkan bahwa, meskipun industri pariwisata Arab Saudi belum mampu menghasilkan pendapatan seperti minyak, tetapi dalam jangka panjang pertumbuhan ekonomi di bawah perubahan hukum yang dibawa oleh Visi Saudi 2030 akan membuahkan hasil. Signifikansi mereka terletak pada penekanan pentingnya sarana hukum yang dikembangkan dengan baik dari kerangka kelembagaan yang kuat untuk keberhasilan implementasi diversifikasi sumber daya ekonomi di ekonomi yang kaya sumber daya yang tidak terbarukan. Ini juga menunjukkan bagaimana reformasi hukum tersebut dapat diterapkan untuk mengejar perubahan ekonomi di negara-negara dengan ekonomi sumber daya dan dapat berfungsi sebagai model bagi ekonomi tersebut yang mengalami masalah serupa.